A Bibliometric Overview of Current States and Research Trends in Concrete-Filled Tube Columns - Ling, Jen Hua; Omoregie, Armstrong Ighodalo (Journal of Civil Engineering, 2025)
Concrete-filled tube (CFT) columns have gained prominence in structural engineering for their exceptional load-bearing capacity and efficiency. This study conducts a bibliometric analysis of 1,154 publications from 2014 to August 2024, using data from the Scopus database and VOSviewer, to map research trends and key developments in CFT studies. Citation, co-citation, and co-authorship analyses identify influential publications, journals, authors, countries, and institutions. Findings highlight significant growth in research output and increasing focus on advanced modelling techniques, including machine learning. Emerging themes include integrating alternative materials such as Fiber-Reinforced Polymer (FRP), stainless steel, High-Performance Concrete (HPC), Recycled Aggregate Concrete (RAC), and Seawater Sea Sand Concrete (SWSSC), showcasing the potential of multi-material innovations. This analysis offers insights into current research directions and identifies gaps, suggesting that future work explore novel material combinations and advanced modelling approaches to enhance performance and drive innovation in CFT column studies.